What is the Ideal Weather for Social Wasp Polistes versicolor (Olivier) go to Forage? - Elisei, Thiago; Nunes, Juliana; Ribeiro Junior, Cleber; Fernandes Junior, Aluisio; Prezoto, Fabio (EntomoBrasilis, 2013)
The objective of this work was to describe the pattern forage of Polistes versicolor (Olivier) waps, verifying the influence of environmental variables on foraging activity. From January to December of 2007, 24 observations of P. versicolor foraging activity in a eucalypt plantation were accomplished. During 10 hours, the intensity of light, wind speed, air humidity and temperature were registered close to the colony. The P. versicolor foraging activity began at 7:30 a.m. and extended to 6:00 p.m. The average departure of workers per hour was 9.62 ±16.67 (0-84), and arrivals per hour were 9.76 ±18.14 (0-87). The most intense activities of the colonies occurred in the period between 10:00 a.m. and 3:00 p.m. The Spearman´s correlation test revealed that the workers’ departures of P. versicolor were stimulated by the increase of light intensity (p< 0.0001) and air temperature p< 0.0001) and the decrease of the humidity (p< 0.0004). The wind speed, however, did not present representative index correlation with the daily activity of the species (p= 0.54). The multivariate linear regression analysis showed that air temperature is the most influential on the P. versicolor foraging activity (p< 0.0001).This study demonstrated that the best weather for P. versicolor departure to forage is a sunshine day, hot temperature and low humidity. In tropical areas these days are common in the summer. Qual o Clima Ideal para Vespa Social Polistes versicolor (Olivier) Sair para Forragear? Resumo. O objetivo deste trabalho foi descrever o padrão de forrageio de Polistes versicolor (Olivier), analisando a influência das variáveis ambientais no forrageio diário. Entre janeiro a dezembro de 2007, foram realizadas 24 observações de colônias de P. versicolor no município de Juiz de Fora, MG, totalizando 240 horas. Durante 10 horas foram registradas, a cada 30 minutos, a intensidade de luz, velocidade do vento, umidade do ar e a temperatura nas proximidades da colônia. A atividade forrageadora de P. versicolor começou às 7h e se estendeu até às 18h. A média de saída para o forrageio por hora foi de 9,62 ± 16,67 (0-84), e a chegada/hora foi de 9,76± 18,14 (0-87). A atividade foi mais intensa no período compreendido entre 10 e 15h. O teste de correlação de Spearman revelou que as trabalhadoras de P. versicolor foram estimuladas a sair pelo aumento da intensidade da luz (p <0,0001), da temperatura do ar (p < 0,0001) e a diminuição da umidade (p <0,0004). Já a velocidade do vento não apresentou índice significativo com a atividade diária da espécie (p = 0,54). A análise de regressão linear múltipla mostrou que a temperatura do ar é a mais influente sobre a atividade forrageadora de P. versicolor (p < 0,0001). O presente estudo revelou que o melhor clima para as operárias de P. versicolor saírem para forragear é com forte intensidade de luz do sol, temperatura elevada e baixa umidade.